PENYELESAIN SENGKETA TANAH ANTARA PT RIAU ANDALAN PULP AND PAPAER DENGAN PETANI KELAPA SAWIT DESA DAYAUN DI KECAMATAN DAYUN KABUPATEN SIAK - Helvicha Ressy; Rika Lestari; Ulfia Hasanah (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2022)
The basis for implementing land use in Indonesia is regulated in Article 33 Paragraph (3) of the 1945 Law, the article explains that everything regarding natural resources including land. Therefore, no one can interfere with someone's land ownership rights, where land tenure rights are a concrete legal relationship. Based on the author's observations, the problem regarding land disputes between PT RAPP and oil palm farmers in Dayun Village is that long-standing mutual claims to land rights have led to even greater conflicts. The purpose of this study was to obtain an overview of the factors causing the dispute between PT RAPP and the oil palm farmers of Dayun Village. And how to resolve land disputes between PT RAPP and oil palm farmers in Dayun Village. It is hoped that the disputing parties should pay attention to and also consider mediation efforts and also other solutions that can reconcile the two parties.